Dependence of overcurrent failure modes of IGBT modules on interconnect technologies - Yaqub, Imran; Li, Jianfeng; Johnson, Christopher Mark (Elsevier, 2015)
Insulated gate bipolar transistor (IGBT) modules which can fail to short circuit mode have great of applications in electricity network related fields. Single IGBT samples have been constructed with the standard Al wire bonding, flexible printed circuit board (PCB) interconnect and sandwich structure technologies. The overcurrent failure modes of the constructed IGBT samples have been tested under a range of energy levels, and the structures of the tested samples have been characterized with scanning electronic microscopy and three-dimensional X-ray computed tomography imaging. The results obtained indicate that the IGBT samples constructed with the three interconnect technologies can fail to both open circuit mode and short circuit mode. The sandwich structure IGBT sample can fail to short circuit mode under an energy level of 750 J which can meet realistic industrial applications. The networked conductive phases within the solidification structure and the Sn-3.5Ag filled in the cracks within the residual Si IGBT are responsible for forming the conducting paths in the tested samples. Both liquid phase and gas phase can be formed and the highest temperature can reach the boiling point of Si even if the sandwich structure IGBT sample is tested with short circuit failure mode.